Facts and Values in the Australian Tax Policy Debate - Fenna, Alan (Taxation Institute of Australia, 2007)
Over the past few years the Howard government has persisted with a policy of incremental change to the personal income tax system despite repeated calls for more fundamental tax reform. Tax reform has been strongly promoted as meaning reduction in top marginal rates and flattening of the income tax scale and as being required for reasons of efficiency and effectiveness. This paper argues that we ought to be sceptical about the ‘tax reform’ agenda – and indeed about the tendentious use of that term itself. Debate has been dominated by one particular set of interests and values whose position is presented in the normatively-neutral language of positive economics.